The Effect of Dividend Yield on The Volatility of Stock Prices of IDX30 Index Companies Listed on the Indonesia Stock Exchange for the 2019-2023 Period - Salsabila Salsabila; Hartaty Hadady; Abdullah W. Jabid; Suratno Amiro; Rusandry Rusandry (Eduvest - Journal of Universal Studies, 2024)
This study investigates the influence of Dividend Yield on Stock Price Volatility in companies included in the IDX30 index on the Indonesia Stock Exchange (IDX) during the 2019-2023 period. Utilizing secondary data from annual reports of IDX30 companies, panel data regression analysis was conducted to examine the relationship between the variables. The findings reveal that Dividend Yield positively affects Stock Price Volatility, contradicting the initial hypothesis. The results indicate that an increase in Dividend Yield leads to higher Stock Price Volatility, while a decrease in Dividend Yield results in lower Stock Price Volatility. This research provides valuable insights for investors in understanding the dynamics between dividend policies and stock price fluctuations.